2015
DOI: 10.1177/0022034515589284
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Dental Biofilms with an Ultrasonically Activated Water Stream

Abstract: Acidogenic bacteria within dental plaque biofilms are the causative agents of caries. Consequently, maintenance of a healthy oral environment with efficient biofilm removal strategies is important to limit caries, as well as halt progression to gingivitis and periodontitis. Recently, a novel cleaning device has been described using an ultrasonically activated stream (UAS) to generate a cavitation cloud of bubbles in a freely flowing water stream that has demonstrated the capacity to be effective at biofilm rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…16 A similar study demonstrated significant decrease in level of Escherichia coli in biofilms formed around medical implants by using gentamicin (72 hours) and ultrasound (48 hours) together. 24 Howlin et al 25 used an ultrasonically activated water stream to remove Streptococcus mutans biofilm and the results revealed that it was very effective as compared with regular water stream alone. However, to date, there is no report on the use of UTS for inhibition of red complex bacteria biofilm, except the present study.…”
Section: Discussionmentioning
confidence: 99%
“…16 A similar study demonstrated significant decrease in level of Escherichia coli in biofilms formed around medical implants by using gentamicin (72 hours) and ultrasound (48 hours) together. 24 Howlin et al 25 used an ultrasonically activated water stream to remove Streptococcus mutans biofilm and the results revealed that it was very effective as compared with regular water stream alone. However, to date, there is no report on the use of UTS for inhibition of red complex bacteria biofilm, except the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it should be performed with ultrasonic instruments, utilising the effects of cavitation 6,13) . This has been shown to be effective in removing biofilms and improving oral hygiene status 8) . …”
Section: Discussionmentioning
confidence: 99%
“…This UAS method has already demonstrated its efficacy in removing dental bacterial biofilms, and cleaning bone, skin models, and removing brain tissue from surgical steel [46][47][48]. Here a range of other applications are shown.…”
Section: Cold Water Cleaning In An Ultrasonically Activated Strementioning
confidence: 99%